Socio-Psychological Aspects of Students’ Digital Health in the Context of Digital Age Challenges - Lomachinska, Irina; Volynets, Iryna; Khrypko, Svitlana (Educological discourse, 2025)
The article presents a comprehensive analysis of the socio-psychological factors influencing the formation of students’ digital well-being in the context of rapid digitalization of social life. The focus is placed on the specific characteristics of today’s student generation, regarded as representatives of the Internet generation, whose socialization and communication predominantly occur in digital environments. Preference is given to electronic forms of interaction, including text messaging, mobile applications, virtual chats, and social networking platforms. This shift toward digital communication alters traditional patterns of interpersonal interaction, affecting young people’s social engagement, cognitive styles, and personal development. Special attention is given to educational strategies among students, who increasingly opt for self-directed learning through digital tools such as video platforms, search engines, online courses, and social media. While these approaches promote new learning models, they also entail various risks. The article explores the adverse consequences of excessive digital activity, including increased technological dependency, sleep deprivation, reduced attention span, heightened anxiety, and a rise in depressive disorders among young people. Constant access to digital devices and online content fosters the emergence of individualistic behavioral patterns in education, communication, and social relationships, which may negatively impact students’ psychological well-being. Within this framework, the concept of "digital health" is clarified as a psychophysiological state shaped by digital lifestyle, which determines an individual’s capacity for safe, conscious, and effective use of digital technologies. The authors identify key psychological threats to students’ digital health, such as nomophobia, information overload, digital stress, a decline in social empathy, as well as the growing incidence of cyberbullying and online harassment, all of which pose serious psycho-emotional risks. The article outlines preventive measures and strategies to preserve digital well-being, including the implementation of educational initiatives aimed at promoting information hygiene, digital detox practices, media literacy, and critical thinking. The conclusion emphasizes the necessity of an interdisciplinary approach to studying the phenomenon of digital health and the formation of a digital culture that integrates technological literacy with reflective thinking, value orientation, and responsible behavior in digital environments as the foundation for students’ balanced personal development.